PENGARUH JUMLAH SUDU DUA DAN SUDU TIGA TURBIN ULIR RUMAH SIPUT VERTIKAL TERHADAP KECEPATAN PUTAR TURBIN - , Salamun, Dr. I Made Miasa, ST., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
. The screw turbine is rarely being used as a Mycrohidro Power Plant In Indonesia, Firstly being used at Bawang sub District, Banjarnegara Regency, Central Java. Though, it does no longer be operated normally. One of the reason was because it speed (the turbine) that rotated 50 RPM, could not reach the speed which been required in about 1500 RPM. Therefore, it would need a high ratio of transmission system with proportion 1:30. Obviously, if it is forced to operate, it will cause high loss both the torsion of the transmission system and the efficiency. By increasing the turning speed of the screw turbine, it is believed could fix those problems. Æ The main purposes of this research are to discover the maximum ability of the screw turbine shape which has a higher turning speed than its prior and to find the effect of two and three blades on the new screw turbine shape of the turbine speed (N), Torsion (T), and Efficiency ( ). While the method of this research is by creating a self-designed turbine shape which has collaboration among propeller turbine, screw turbine and Open Flume turbine. This method was tested in lab by adapting all the needs. An approximation of the propeller turbine calculation is used to calculate the turbine dimension. turbin ulir rumah siput The result of this research about the collaboration among propeller turbine, screw turbine and Open Flume turbine which called â vertikalâ was invented. On the âturbin ulir rumah siput vertikalâ the two blades has both a higher torsion and efficiency than three blades. While on the three blades has a higher turns than the previous.